2018
DOI: 10.2967/jnumed.117.202937
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Voxel-Based Dosimetry for Assessing the Ability of the Body-Surface-Area Model to Predict Delivered Dose and Radioembolization Outcome

Abstract: The aim of this study was to quantitatively evaluate the ability of the body-surface-area (BSA) model to predict tumor-absorbed dose and treatment outcome through retrospective voxel-based dosimetry. Data from 35 hepatocellular carcinoma patients with a total of 42Y-resin microsphere radioembolization treatments were included. Injected activity was planned with the BSA model. Voxel dosimetry based on Tc-labeled macroaggregated albumin SPECT andY-microsphere PET was retrospectively performed using a dedicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…However, pre-treatment activity planning based on 99m Tc-MAA lacks dosimetric accuracy and needs improvement in order to increase the clinical benefit of radioembolization treatment. A recent study by Kafrouni et al showed that body surface area (BSA) based activity planning (i.e., the "BSAmethod") often leads to under-dosing, most likely because it insufficiently corrects for the tumor-to-normal (T/N) uptake ratios [21]. Despite this limitation, the BSA-method currently is the most commonly used treatment planning method [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, pre-treatment activity planning based on 99m Tc-MAA lacks dosimetric accuracy and needs improvement in order to increase the clinical benefit of radioembolization treatment. A recent study by Kafrouni et al showed that body surface area (BSA) based activity planning (i.e., the "BSAmethod") often leads to under-dosing, most likely because it insufficiently corrects for the tumor-to-normal (T/N) uptake ratios [21]. Despite this limitation, the BSA-method currently is the most commonly used treatment planning method [22].…”
Section: Discussionmentioning
confidence: 99%
“…It was in good agreement with the treated liver lobe or liver segment, when displayed with the corresponding CT and MR images as verified by an experienced nuclear medicine physician. The quantitative whole liver 99m Tc-MAA SPECT/CT was divided by the total administered 99m Tc activity and then scaled with the total administered 90 Y therapy activity within the treated liver volume VOI using an in-house developed MATLAB code (R2018b; The MathWorks, Inc. Natick, MA), similar to the normalization approach by Kafrouni et al [39]. Outside the VOI of the treated liver volume, the image contents were set to zero.…”
Section: Dosimetry Calculation 231 Generation Of Absorbed Dose Imagesmentioning
confidence: 99%
“…Dieudonné et al reported the feasibility of voxel-based three-dimensional (3D) dose mapping based on 99m Tc-MAA single-photon emission computed tomography (SPECT)/computed tomography (CT) performed for pretreatment planning of yttrium-90 ( 90 Y) microsphere TARE [9]. Kafrouni et al demonstrated the correlation between treatment response and mean absorbed radiation dose derived from voxel-based dosimetry based on post-treatment 90 Y-microsphere positron emission tomography (PET) [10].…”
Section: Introductionmentioning
confidence: 99%